2017
DOI: 10.1016/j.healun.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Low ejection fraction in donor hearts is not directly associated with increased recipient mortality

Abstract: Recipients of hearts with reduced EF have equivalent 1-year survival compared with recipients of hearts with normal EF. Donor hearts with reduced EF show significant functional recovery after transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 15 publications
2
44
1
3
Order By: Relevance
“…A recent UNOS registry analysis used propensity score analysis to examine post-operative outcomes of recipients of donor hearts with left ventricular ejection fraction <40% (reduced), 40-50% (borderline), and ≥50% (normal) and showed equivalent odds of primary graft failure and death at 1 year in all 3 groups. At 1-year post-transplant, the mean ejection fraction was normal in recipients of donor hearts with reduced systolic function (24). There is certainly a concern for selection bias in such studies, as we cannot know the outcomes of donor hearts with left ventricular dysfunction that were declined for transplantation.…”
Section: Donor Left Ventricular Dysfunctionmentioning
confidence: 99%
“…A recent UNOS registry analysis used propensity score analysis to examine post-operative outcomes of recipients of donor hearts with left ventricular ejection fraction <40% (reduced), 40-50% (borderline), and ≥50% (normal) and showed equivalent odds of primary graft failure and death at 1 year in all 3 groups. At 1-year post-transplant, the mean ejection fraction was normal in recipients of donor hearts with reduced systolic function (24). There is certainly a concern for selection bias in such studies, as we cannot know the outcomes of donor hearts with left ventricular dysfunction that were declined for transplantation.…”
Section: Donor Left Ventricular Dysfunctionmentioning
confidence: 99%
“…5,11 This is supported by both experimental 12 and clinical 10,[13][14][15] evidence in adults that hearts damaged by brain-death pathophysiology are capable of functional resuscitation. We, and others, have also demonstrated that hearts with poor ventricular function can be transplanted in both the pediatric [16][17][18] and adult [19][20][21][22][23] populations, with results equivalent to those seen for normally functioning donor hearts.…”
mentioning
confidence: 66%
“…Furthermore, our parameters for the ideal donor heart are far more restrictive than current practice, especially with regard to normal ejection fraction, as there are data to support that lower ejection fraction hearts are acceptable organs, especially when procured from young donors. 25,26 In addition, our study was limited by the small volume of DCD donor information available for review. Finally, given the sensitivity of detailed donor information, one-time chart review of DCD donors in Region 9 that were not accessed for clinical reasons limited our ability to expand this study to other Regions in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our parameters for the ideal donor heart are far more restrictive than current practice, especially with regard to normal ejection fraction, as there are data to support that lower ejection fraction hearts are acceptable organs, especially when procured from young donors 25,26. If this number were to increase by even 2-fold, this would yield a significant increase in the heart donor pool, suggesting that our study likely underestimates the potential of DCD donation.…”
mentioning
confidence: 93%